EVALUATION OF SERUM ANGIOTENSIN CONVERTING ENZYME, OXIDATIVE STRESS, AND ANTIOXIDANT LEVELS IN CEREBROVASCULAR DISORDERS AND HEALTHY CONTROL – A COMPARATIVE STUDY - KAUR, JASPREET; MITTAL, MRIDULA; GUPTA, VISHAL; KAUR, JASWANT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Several studies indicate the existence of an abnormal balance between the oxidative and protective mechanisms in patients can be a causative factor for cerebrovascular disease. High plasma levels of angiotensin-converting enzyme (ACE) contribute to the development of vascular diseases. Serum ACE and antioxidant levels were determined in cerebrovascular disorders (CVD) and compared between CVD and healthy person. Methods: A cross-sectional study was conducted on 50 cases of stroke and 10 cases of transient ischemic attack (TIA) with 60 controls matched for age and sex. Fasting blood samples were estimated for serum angiotensin-converting enzyme, serum lipid profile, MDA, SOD, and serum Vitamin E). ACE was estimated by spectrophotometry. The levels of ACE were correlated with the severity and outcome of the stroke. Results: The level of serum ACE was significantly higher in stroke (27.50±1.14U/L) and TIA (31.60±2.02 U/L) as compared to controls (22.61±0.79 U/L). Fasting blood sugar, total cholesterol, triglycerides, LDL cholesterol, and MDA were significantly increased whereas a significant decrease was observed in serum HDL, erythrocyte SOD, and Vitamin E levels in cerebrovascular disease patients as compared to the control group. Statistical p<0.05 was considered significant. Conclusion: Oxidative stress is a potential contributor to acute ischemic stroke and TIA besides deranged lipid profile. The oxidant-antioxidant imbalance may contribute to the severity of stroke. The levels of serum ACE increase significantly in stroke and TIA patients and are associated with increased severity and worse outcome of cerebrovascular diseases.